Polyphemus Moth Antheraea polyphemus (Cramer) (Insecta: Lepidoptera: Saturniidae: Saturniinae) - Donald W. Hall (EDIS, 2012)
The polyphemus moth, Antheraea polyphemus (Cramer), is one of our largest and most beautiful silk moths. It is named after Polyphemus, the giant cyclops from Greek mythology who had a single large, round eye in the middle of his forehead. The name is because of the large eyespots in the middle of the moth’s hind wings. This 9-page fact sheet was written by Donald W. Hall and published by the UF Department of Entomology and Nematology, August 2012.